Mood, Dimensional Personality, and Suicidality in a Longitudinal Sample of Patients with Bipolar Disorder and Controls. Issue 5 (19th November 2018) - Kamali, Masoud; Saunders, Erika F. H.; Assari, Shervin; Ryan, Kelly A.; Marshall, David F.; McInnis, Melvin G.
Abstract : Objective: To evaluate the effects of mood and anxiety symptoms in relation to personality dimensions and clinical features such as trauma and substance use on suicidal behaviors in a longitudinal sample of individuals with bipolar illness (BP) and healthy controls (HC). Methods: Mood, personality, and clinical features were assessed in 151 individuals with BP I and 119 HC. Clinical data were collected at baseline and at 2‐year follow‐up. Personality traits were measured using the NEO PI‐R. Results: In bivariate analyses, personality measures were significantly different between BP and HC, and between BP based on suicide attempt history. However, in regression analyses, baseline measures of depression, mania, anxiety, trauma, education, and age of BP onset correlated with personality domains, while a history of suicide attempts did not. Logistic regressions showed that prospective depression or mania, and a pattern of mixed mood features and chronicity of illness, along with two Neuroticism facet scores (N4—Self‐Consciousness and N6—Vulnerability) were predictive of suicide ideation (SI) in the 2‐year follow‐up period. Conclusions: While dimensions of personality, trauma, and substance use clearly correlated with suicidal behaviors in BP, in multivariate models emerging mood symptoms were the most robust predictors of suicidality. These results reinforce the importance and attributable role of mood and anxiety symptoms in evaluating suicidal risk.